2018
DOI: 10.3390/jfmk3010009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resistance Training on Telomere Length in Women Recovering from Breast Cancer

Abstract: Abstract:The purpose of this exploratory analysis was to examine the effects of resistance training (RT) on leukocyte telomere length in breast cancer survivors. Samples from 33 breast cancer survivors were analysed following a 16-week RT or usual care intervention (RT: n = 19, control: n = 14). The RT group performed supervised exercise three times per week. Leukocyte telomere length was assessed before and after training using quantitative PCR. Changes in telomere length were analysed using ANCOVA, with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In addition, there are studies that focus mainly on resistance exercise gain with contradictory results. Some research has shown that endurance training causes adaptive changes in the antioxidant protein systems at the systemic level leading to a maintenance of TL [ 42 ], while other studies have concluded there is no effect at all [ 43 , 44 ] or even a shortening of TL [ 45 ]. Nevertheless, in this work we observed that in those subjects who had participated in a program involving both types of exercise (Aerobic exercise + Resistance exercise) there was an increase in TL 6 months after the program had ended.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are studies that focus mainly on resistance exercise gain with contradictory results. Some research has shown that endurance training causes adaptive changes in the antioxidant protein systems at the systemic level leading to a maintenance of TL [ 42 ], while other studies have concluded there is no effect at all [ 43 , 44 ] or even a shortening of TL [ 45 ]. Nevertheless, in this work we observed that in those subjects who had participated in a program involving both types of exercise (Aerobic exercise + Resistance exercise) there was an increase in TL 6 months after the program had ended.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that only LV-HIIT (a type of cardiovascular exercise), but not the strengthbased exercise types (1-RT and WB-EMS) improved TL is in line with the study by Werner et al [20], who reported that TL increased after 6 months of aerobic endurance and interval training in previously sedentary but otherwise healthy individuals, but not with resistance training. Additionally, two other RCTs that implemented resistance training as a form of exercise intervention in breast cancer survivors [99] and in elderly individuals [103] did not observe a significant impact on TL. Thus, although it is undisputed that resistance training is an essential part of a well-rounded exercise routine as it is the most effective method to maintain/increase muscle mass and strength [104] and is independently associated with reduced mortality risk [105], our data support previous findings suggesting that resistance training alone may not be a sufficient stimulus to produce significant changes in TL.…”
Section: Discussionmentioning
confidence: 89%
“…However, it is important to note that only a few RCTs have been conducted to evaluate the effects of targeted exercise interventions on TL. These trials have yielded inconsistent findings, with five studies reporting beneficial effects on TL [20,[94][95][96][97] following a specific exercise intervention, while six studies did not observe significant changes in TL [98][99][100][101][102][103]. The conflicting results could mainly be due to the different exercise modalities used in previous RCTs, as seven studies applied continuous aerobic training regimens [20,94,97,98,[100][101][102], three studies utilized interval training protocols [20,95,96], and three studies employed resistance training programs [20,99,103].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They did, however, reveal an inverse correlation between personal best strength achievements and TL. Although considered a safe an effective intervention for improving quality of life and muscular strength, Hagstrom and Denham (2018) found that a 16-week resistance training intervention did not alter leukocyte TL in women recovering from breast cancer compared to a control group. Given that telomeres gradually shorten with aging, longer interventions will be required to investigate any meaningful exercise-induced changes in TL in longitudinal studies.…”
Section: Effect Of Resistance Training On Dna Damage Dna Methylation and Telomere Lengthmentioning
confidence: 94%